The Role of Perceptual Interference, Semantic Interference, and Relational Integration in the Development of Analogical Reasoning - Yu, Xiao; Geng, Liuna; Chen, Yinghe; Han, Congcong; Zhu, Xiaojing (Frontiers in Psychology, 2020)
This study aimed to examine the role of perceptual interference, semantic interference and relational integration in the development of analogical reasoning, and to compare the interactive pattern of interference and relational integration (RI) in children and adults. In Experiment 1, we tested thirty-one 3-and 4-year-olds, twenty-seven 5- and 6-year-olds, and forty adults for perceptual interference and relational integration in analogical reasoning. Perceptual interference emerged when proper mapping between analogically matching objects was incoherent with their perceptual features. Relational integration was evaluated via manipulation of the number of objects in an analogical scene. Significant main effects of perceptual interference and relational integration were found in children and adults. In Experiment 2, we tested thirty 3- and 4-year-olds, twenty-seven 5- and 6-year-olds, and forty adults for semantic interference and relational integration in analogical reasoning. Semantic interference emerged when proper mapping between analogically matching objects was incoherent with their categorical features. Results showed significant main effects of semantic interference and relational integration in children and adults. The results of both experiments suggested different mechanisms of interference and relational integration in children and adults. For children, interference and relational integration depended on shared cognitive sources. If one factor (i.e., interference resolution) needed more cognitive demand, there would be limited resources available for another factor (i.e., relational integration). Furthermore, for adults, the increased load of relational integration and interference on adults’ analogical reasoning exceeded the sum of their respective singular effects. For 3- and 4-year-olds, the degree of perceptual interference was larger than the degree of semantic interference in the Binary Relation condition, while there was no significant difference between the degree of two types of interference in the Quaternary Relation condition. Moreover, for 5- and 6-year-olds, the degree of semantic interference was larger than the degree of perceptual interference in both relation conditions. For adults, there was no difference between the degree of two types of interference in both relation conditions. The article also discusses the theoretical and practical implications of this research.